(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Effective cleaning necessitates the reduction or elimination of toxicity, the use of plants to remove or detoxify environmental pollutants, or the immobilization of the pollutants in the growth matrix in the soil through biological and biological nature, chemical, or physical activities or processes somewhere in the city of Baghdad, the current situation. Because minerals cannot disintegrate and element concentrations are high, it takes a while for the mechanisms to reduce the percentage of mineral contamination in soils (Cd, Cr, Fe ), to determine the association between plants using an average of data from plants that varied from one another in terms of their capacity to absorb lead and the concentration in three key plant types. Eucalyptus camaldulensis, Cupressus dupreziana, (0.033, 0.018)ppm. The elements may dissolve in water, which could lead to their migration into the soil and up the food chain. Many industrial activities, such as mining, mineral processing, and chemical production, result in an increase in the concentration of nonessential minerals in the water levels in the areas surrounding industrial sites.